2019
DOI: 10.7759/cureus.5252
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Eosinophilic Esophagitis in Patients with Refractory Gastroesophageal Reflux Disease

Abstract: IntroductionEosinophilic esophagitis (EoE) is not a common differential diagnosis in patients with longstanding refractory gastroesophageal reflux disease (GERD). The aim of this retrospective analysis was to assess the prevalence of EoE in patients with refractory GERD.MethodsThis retrospective analysis was performed in the Gastroenterology Department of a tertiary care institute in Karachi, Pakistan. Records of esophagogastroduodenoscopy (EGD) with esophageal biopsy from January 2016 till December 2018 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…All patients had 'feline oesophagus' on endoscopy with micro-abscesses visible in some, with a history of atopy, complaints of dysphagia and food impaction. [15] Comparable to the above mentioned results of previous studies, our studies presented the same results that prevalence of EoE among GERD patients was 9%. Only a few studies have looked at the possibility of GERD and EoE coexisting.…”
Section: Discussionsupporting
confidence: 89%
“…All patients had 'feline oesophagus' on endoscopy with micro-abscesses visible in some, with a history of atopy, complaints of dysphagia and food impaction. [15] Comparable to the above mentioned results of previous studies, our studies presented the same results that prevalence of EoE among GERD patients was 9%. Only a few studies have looked at the possibility of GERD and EoE coexisting.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study found that EE can relapse within 2 weeks after stopping PPIs, with some patients even developing LA grade C EE (63). EoE has been seen in 1%-8% of patients with refractory GERD (24,(167)(168)(169)(170). Temporarily discontinuing PPIs before endoscopy in these patients may unmask the EoE histology, which could be obscured if endoscopy is performed on PPIs, missing an opportunity to identify the cause of ongoing GERD symptoms.…”
Section: Endoscopymentioning
confidence: 99%
“…Our results were in agreement with others (24) , who observed that the main symptoms experienced by patients were heartburn (80.8%), regurgitation (65.8%), and atypical symptoms (53.4%). However, Anis et al (25) reported that dysphagia was the chief complaint leading to EGD followed by food impaction and heartburn.…”
Section: Discussionmentioning
confidence: 99%